Trends in atmospheric deposition fluxes of sulphur and nitrogen in Czech forests - Hůnová, Iva; Maznová, Jana; Kurfürst, Pavel (Environmental pollution (Barking, Essex, 2014)
We present the temporal trends and spatial changes of deposition of sulphur and nitrogen in Czech forests based on records from long-term monitoring. A statistically significant trend for sulphur was detected at most of the sites measuring for wet, dry, and total deposition fluxes and at many of these the trend was also present for the period after 2000. The spatial pattern of the changes in sulphur deposition flux between 1995 and 2011 shows the decrease over the entire forested area in a wide range of 18.1-0.2 g m(-2) year(-1) with the most pronounced improvement in formerly most impacted regions. Nitrogen still represents a considerable stress in many areas. The value of nitrogen deposition flux of 1 g m(-2) year(-1) is exceeded over a significant portion of the country. On an equivalent basis, the ion ratios of NO3(-)/SO4(2-) and NH4(+)/SO4(2-) in precipitation show significantly increasing trends in time similarly to those of pH.
Keywords: stromy; Environmental Monitoring; Sulphur; látky znečišťující vzduch; znečištění ovzduší; monitorování životního prostředí; síra; Trees; Česká republika; Nitrogen; Air Pollution; dusík; Air Pollutants; Forests; Atmospheric deposition; Czech Republic; Sulfur